Dynamic Response Analysis of Parallel Twin Tunnels Under Different Train Loads - Lin Wu; Jiayan Wang; Xiaoya Bian; Hong Guo (Applied Sciences)
Due to the spatial constraints of underground environments, the spacing between dual-line tunnels in urban metro systems is often limited, leading to potential mutual interference during the operation of trains in closely spaced parallel tunnels. In this study, a twin-tunnel model was developed using PFC2D to simulate the variations in displacement, velocity, porosity, and strain of the T2 structure and its surroundings under eight conditions (Fi = 62.4–131.5 kN, i = 1, 2, 3…, 8), elucidating the static and dynamic responses of the adjacent tunnel structure and its surroundings. The results indicate that the vertical response of T2 sleepers is significantly larger than the horizontal response under the same load. Increasing train loads induce non-uniform deformation in T2 liners, and excessive overloading may result in microcracks or structural failure. The velocity and displacement at the ground surface are substantially more significant than those in the surrounding areas closer to the vibration source, primarily due to the surface amplification effect. The surroundings of the adjacent tunnel experience uneven compressive forces, potentially causing liner separation. Under the A7 condition, the static and dynamic responses of the tunnel structure and its surroundings sharply decreased due to the combined effects of pressure and train load dynamics. This phenomenon is attributed to the interplay between the pressure effect and the dynamic amplification effect of the train load. It is recommended that the operational train load in practical engineering should not exceed the A4 condition (92.0 kN). This study can provide a reference for analyzing the static and dynamic responses of twin-tunnel structures under metro overloading conditions.